Students' adoption of e-learning in emergency situation: the case of university of jaffna during covid – 19 - Sriranjan, A. (University of Jaffna, 2022)
Purpose: This study aims to investigate the antecedents of student e-learning among undergraduates in the Faculty of Management Studies and Commerce, University of Jaffna, during the Covid – 19 period, using widely accepted social psychology theories. Methodology: This research tested a conceptual framework derived from widely accepted theories. Questionnaire data were based on a sample of 257 undergraduates from the Faculty of Management Studies and Commerce, University of Jaffna. The suggested research model was tested by using the quantitative way of analysis (Regression analysis) to examine the proposed hypothesis of this inquiry. Furthermore, online questionnaires are distributed to all participants during the period of COVID – 19 and imposed locked down in Sri Lanka. Findings: The theoretical model was validated within the context of a single empirical study. The Findings provided significant statistical support for the research model. The results of the structural model show that Social Influence (SI), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude (ATT) have a positive impact on Student behaviour Intention (BI) towards e-Learning adoption. Surprisingly, the authors documented that Facilitating Conditions (FC) have no significant impact on students' Behaviour intention (BI) and Social Influence (SI) can moderately affect Behaviour Intention (BI). The Attitude (ATT) has a direct impact on the student's Behaviour Intention (BI) toward e-Learning adoption. Research limitations: This study focuses on five independent variables; future researchers should consider more independent variables. In the future, the longitudinal study could be undertaken by the researchers to eliminate the method bias and to investigate the relationships between the constructs. Furthermore, other methods in well-established studies should be applied in the future. Implications: This study has both theoretical and practical implications. From a theoretical perspective, the study can provide a solid framework for similar studies. From a practical perspective, this study offers implications for governments and universities in the process of adopting e-learning, given that the Covid-19 pandemic is currently in its multi-waves and other similar situations. Importantly, the Researcher focuses on the implications for the studied institution regarding the implementation of e-learning in an emergency as well as provides insights for the University of Jaffna.
Keywords: E-learning; Intention to use; Technology acceptance model